Morbidity and Mortality of Eastern Barn Owls (Tyto javanica) Admitted to a Southeast Queensland Wildlife Hospital - Robert Doneley; Ashleigh Hicks; Andrew Hill (Veterinary Sciences)
The eastern barn owl (Tyto javanica), a sub-group of Tyto alba, the most common species of owl in the world, is classified as “of least concern” under Queensland (Australia) legislation but appears to be affected by urban development. Between August 2010 and December 2021, 412 wild eastern barn owls were presented for treatment to the Currumbin Wildlife Hospital. A retrospective study of their medical records shows a strong association between the season and the number of admissions, with a combined total of 80% of admissions occurring in winter and spring (the breeding season for this species) in southeast Queensland. There was no significant association between age and admissions. The most common diagnosis was traumatic injuries, especially in winter and spring. Of all admissions, 46.61% died or were euthanized, 36.17% were transferred to wildlife carers, and 13.83% were discharged from the hospital. We postulate that the breeding season results in an increase in the owls’ activity, in turn resulting in greater risk exposure and increased admissions to veterinary clinics. These findings confirm that and thus provide information about the vulnerability of this species to anthropogenic activities and the implications for outcomes of injured owls.